LEVOSULPIRIDE IN PREMATURE EJACULATION - Hussain, Syed Javid; Hameed, Atif; Nazar, Hassan Shahzad; Javid, Ania; Shah, Yousaf; Hameed, Waqas; Miran, Muhammad Shah (Journal of Ayub Medical College Abbottabad, 2010)
Background: Premature ejaculation is one of the most common sexual disorders. A large number of treatment options have been used so far for the treatment of this dysfunction and still a large number of experts are doing research in this field. Here we have tried to research on the beneficial effects of levosulpiride in the treatment of PE. Methods: Eighty-eight patients form different areas of Hazara division suffering from PE were chosen. Sixty-four patients were given levosulpiride and the remaining 24 patients were given Placebo. Results: Out of 64 patients who have been given levosulpiride, 30 patients showed very good improvement, 14 patients showed some improvement, 14 patients showed little and 06 patients showed no improvement. Conclusion: levosulpiride have very good beneficial effects in the treatment of PE. Keywords: levosulpiride, premature ejaculation